PAMERAN BUKU BERSAMA KOMUNITAS SATU PENA UNTUK MENGGERAKKAN LITERASI MEMBACA - Rahmatika Aini, Miza; Moelia, Edya (JICS : Journal Of International Community Service, 2024)
Lately, reading literacy activities have become less popular among the younger generation. Children began to switch to playing cell phones or gadgets rather than reading books. By reading a lot, children will actually increase their knowledge. This knowledge will help them overcome various things. The more we read, the more knowledge we gain. The book exhibition activity with Komunitas Satu Pena is a means to improve students' reading literacy. There are several stages in the implementation of this book exhibition. The preparation stage was carried out around March-April. The preparation stage was carried out in the form of a meeting which determined the Book Exhibition event which was held in May. The exhibition implementation stage will be carried out in May, but the date has not yet been agreed upon. The exhibition will be held at Taman Siswa Batu City. At the implementation stage, the committee is from the author, the East Java One Pen Community and several Unisba students. In its implementation, Unisaba students in the 4th semester of the Literature Appreciation course made an anthology of poems published in one pen. Then the anthology was read together at a book exhibition and literacy workshop.